Gambaran perawatan diri pada pasien hipertensi di puskesmas Kalijati Subang - Isania Nuril Aini; Rosiah Rosiah; Minanton Minanton (Vitamin : Jurnal ilmu Kesehatan Umum, 2024)
Hypertension is a non-communicable disease characterized by an increase in blood pressure above normal limits. Hypertension is a disease that increases every year and can cause complications. Hypertension can be prevented from complications by doing good self-care to control blood pressure. Self-care is an action taken independently to improve health, prevent disease and maintain health. Here are 5 components of self-care for people with hypertension, namely self-integration, self-regulation, interaction with health workers and others, monitoring blood pressure, and adherence to recommended rules. The purpose of this study was to determine the description of self-care in hypertensive patients at Puskesmas Kalijati Subang. This research design is descriptive with cross sectional design. The population in this study was 921 people, where the research sample was 91 people. The sampling technique used purposive sampling. The results of this study found that self-care in hypertensive patients at Kalijati Subang Health Center was 61.5% in the bad category and 38.5% in the good category. The conclusion is that most of the self-care in hypertensive patients at Puskesmas Kalijati Subang is in the bad category. It is hoped that future researchers can develop related factors that affect self-care in hypertensive patients.